(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
This paper makes an effort to provide a framework for good governance in India by identifying its essential features and shortcomings in its working and emphasizes need for innovative approaches. No theory of governance could be intelligible unless it is seen in the context of its time. India’s democratic experience of the past six decades has clearly established that good governance must aim at expansion of social opportunities and removal of poverty. Good governance, according to the author, means securing justice, empowerment, employment and efficient delivery of services.In recent years, courts have risen in power across the world, and the Indian Supreme Court has rightly been pointed to as an example of this global trend. In many ways the Indian Court has become a court of good governance that sits in judgment over the rest of the Indian government. This Article argues that the Court has expanded its mandate as a result of the shortcomings (real, perceived, or feared) of India’s representative institutions. The Indian Supreme Court’s institutional structure has also aided its rise and helps explain why the Court has gained more influence than most other judiciaries.